Vermelho e negro: Beleza, sentimentos e proteção entre os Tapirapé - Damas, Vandimar Marques (2016)
The aim of this thesis is to ponder on the relationship among the production of artifacts, body painting, and shamanism amongst the indigenous people Tapirapé - auto denomination Apyãwa- and how this knowledge is intertwined and shared within and outside the village. The methodology used in this paper is the field work conceded in the Tapi'itãwa village, located in the territory of Urubu Branco MT, with records in the field’s diary, photographic and audiovisual. Tapirapé has its roots on the Tupi language, and its territory is located in the northeastern state of Mato Grosso. The research was based on Wagley Charles (1988), Baldus Hebert (1972) and Els Lagrou (2007) works as the main theoretical references to produce this ethnography. The body painting here is understood as the reasons executed on the bodies of people, and these reasons are present both in the bodies of people, but also in the masks, bowls and other artifacts produced by the Tapirapé. The Shaman is the chief warrior and he has the power of healing, of disease, and death. In addition, the shaman is responsible for protecting the village. Body painting as artifacts and shamanism operate in the bodies among Tapirapé. Finally, I believe in the Shaman as a demiurge as it connects the visible and invisible to grasp and pass on the knowledge to the Tapirapé. Therefore, if the Shaman is responsible for bringing this knowledge, the school appears as an organization that contributes to the preservation and transmission of knowledge. Nonetheless, the school is not exempt of critics among the Tapirapé. Also, the insertion of artifacts in museums generates debate on how to place and how to expose these artifacts. The image is one of the components of this ethnography, as well as the photographs in this paper, and of course the shamanism and the rituals that also denote to images. Furthermore, this research contains two videos about Tapirapé body painting and shamanism.